Superman II [videorecording (DVD)] - Reeve, Christopher; Hackman, Gene; Kidder, Margot; Beatty, Ned; Puzo, Mario, 1920-1999; Newman, David; Newman, Leslie; Spengler, Pierre, 1947-; Lester, Richard; Salkind, Alexander, 1922-1997; Salkind, Ilya, 1947-; Shuster, Joe, 1914-1992; et al. (Warner Bros. Entertainment : Distributed by Warner Home Video, 2009)
Sequel to 'Superman', this time the Man of Steel is battling three villains from his home planet.